Towards an Understanding of the Herpes Simplex Virus Type 1 Latency-Reactivation Cycle - Perng, Guey-Chuen; Jones, Clinton (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Infection by herpes simplex virus type 1 (HSV-1) can cause clinical symptoms in the peripheral and central nervous system. Recurrent ocular shedding can lead to corneal scarring and vision loss making HSV-1 a leading cause of corneal blindness due to an infectious agent. The primary site of HSV-1 latency is sensory neurons within trigeminal ganglia. Periodically, reactivation from latency occurs resulting in virus transmission and recurrent disease. During latency, the latency-associated transcript (LAT) is abundantly expressed. LAT expression is important for the latency-reactivation cycle in animal models, in part, because it inhibits apoptosis, viral gene expression, and productive infection. A novel transcript within LAT coding sequences (AL3) and small nonprotein coding RNAs are also expressed in trigeminal ganglia of latently infected mice. In this review, an update of viral factors that are expressed during latency and their potential roles in regulating the latency-reactivation cycle is discussed.